If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2x = 2x + 7 + x Reorder the terms: 10 + -2x = 7 + 2x + x Combine like terms: 2x + x = 3x 10 + -2x = 7 + 3x Solving 10 + -2x = 7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 10 + -2x + -3x = 7 + 3x + -3x Combine like terms: -2x + -3x = -5x 10 + -5x = 7 + 3x + -3x Combine like terms: 3x + -3x = 0 10 + -5x = 7 + 0 10 + -5x = 7 Add '-10' to each side of the equation. 10 + -10 + -5x = 7 + -10 Combine like terms: 10 + -10 = 0 0 + -5x = 7 + -10 -5x = 7 + -10 Combine like terms: 7 + -10 = -3 -5x = -3 Divide each side by '-5'. x = 0.6 Simplifying x = 0.6
| 49(2n+5)=37(3n+1) | | 15+6z=9 | | 49(2n+5)=37(n+1) | | 1/3*12/x-8=-1 | | 45(8n-3)=19(2n+7) | | 2z^2-4z+4=0 | | 16=2x+5y | | y=5ln(3x-2) | | x^2+2*x-3=0 | | y=tan(3+X) | | 8x*1,4=4x | | 9m-13=-8 | | 4a+(-3)-2a=-4a-3 | | 6(x-3)=2 | | 4(8+x)=50 | | -2(5c+6)=8(3-c) | | (1/5)*x=1/125 | | 1/3x=1/9 | | 8x-(3x+6)=15 | | 7x^2+48x+68=0 | | 16b-60=5(5b-3) | | -8t+7=-7t+4 | | 1/3x=-1/3 | | .45x+.85x+12=1.05x | | -x^2+3=4x-1 | | 9n-9-3n= | | x^2+4xy-4x=0 | | (x-6)+(y+7)=85 | | 2x+900=2 | | x^2+4xy-4x-4=0 | | 2cos(4x+60)-1=0 | | 7a+3a+4a= |